2018
DOI: 10.1055/a-0735-9641
|View full text |Cite
|
Sign up to set email alerts
|

Altering Physical Activity Influences Insulin Responses to Glucose Ingestion in Healthy Adults

Abstract: This study determined if varying physical activity (PA) the day prior to an oral glucose tolerance test (OGTT) differentially influenced postprandial glucose and insulin kinetics. Fifteen healthy, young adults participated in three OGTT trials the morning after performing 50% (LOW), 100% (HABITUAL), or 150% (HIGH) of their habitual PA (determined by 7-day pedometry). Trials were randomized and separated by at least 1-wk. For each OGTT trial, blood glucose and insulin were measured after an overnight fast and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These lipid molecules are mainly composed of sphingosine and are a significant component of the cellular lipid bilayer membrane by an essential role in maintaining its integrity [ 117 ]. Ceramide synthesis occurs in at least three distinct ways as the de novo pathway, the sphingomyelin hydrolysis (degradation), and the salvage (recycling) pathway [ 8 ]. In addition to structural roles, more recent studies have suggested a causal relationship between ceramide and metabolic complications as well as insulin resistance [ 118 ].…”
Section: Pathophysiologic Links Between Physical Inactivity and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…These lipid molecules are mainly composed of sphingosine and are a significant component of the cellular lipid bilayer membrane by an essential role in maintaining its integrity [ 117 ]. Ceramide synthesis occurs in at least three distinct ways as the de novo pathway, the sphingomyelin hydrolysis (degradation), and the salvage (recycling) pathway [ 8 ]. In addition to structural roles, more recent studies have suggested a causal relationship between ceramide and metabolic complications as well as insulin resistance [ 118 ].…”
Section: Pathophysiologic Links Between Physical Inactivity and Insulin Resistancementioning
confidence: 99%
“…But substantial changes in modern lifestyle towards lower physical activity have also increased the prevalence of DM in young adults [ 6 , 7 ]. Furthermore, there is a positive relationship between long-term physical inactivity and insulin resistance [ 4 , 8 ]. But the exact linking pathophysiologic pathways are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetarian diets are also associated with lower insulin resistance and lower fasting insulin levels, even in comparison with matched lean controls, and appear to improve healthspan and possibly also lifespan ( 74 , 75 ). Another lifestyle parameter associated with better healthspan is physical exercise, which causes lower fasting and post-challenge insulin levels as well as improved insulin sensitivity ( 76 78 ).…”
Section: Insulin and Aging: Epidemiological Findingsmentioning
confidence: 99%